Penggunaan Data Mining untuk Analisis Pola Pembelian Pelanggan Menggunakan Metode Association Rule Algoritma Apriori (Studi Kasus di Toko Waspada) - Saparudin, Mohamad Gusmil; Sholihin, Sholihin (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Alert Shop is a store that sells a variety of products such as household items, daily necessities, accessories, and cosmetics. Analyze customer buying behavior with Alert Store bulk transaction data.. The Apriori algorithm is one of the algorithms for extracting correlation rules in the field of data mining. We apply the Apriori algorithm by using Rapid Miner to find customer buying patterns in Waspada Store sales transaction data. The methodology of this research is structured to serve as a reference for the researcher's guidance and support to the researcher in the research process, and the research design plays an important role in guiding the researcher from problem description to testing result. The rules used by the a priori algorithm can be used as criteria to evaluate elements that meet the minimum support and minimum confidence values. The confidence value of the relationship between the two points above can be considered high, and the results of these rules can be used as the basis for discussing the points above.